2018
DOI: 10.1038/s41598-018-32911-3
|View full text |Cite
|
Sign up to set email alerts
|

A magnetically recyclable photocatalyst with commendable dye degradation activity at ambient conditions

Abstract: An efficient, economical, environment-friendly and easy separable catalyst to treat environmental contaminants is an enduring attention in recent years due to their great potential for environmental protection and remediation. Here we have reported the excellent performance of polyaniline activated heterojunctured Ni0.5Zn0.5Fe2O4 catalyst to degrade azo dye in an aqueous solution at ambient condition. The catalyst was prepared via a simple facile polymerization procedure. The physicochemical properties and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Discharge of chemically stable and non-biodegradable toxic organic dyes into aquatic environments is a growing problem because of their highly toxic nature 1,2 . Organic dyes can affect the oxygen dissolution, sunlight penetration, and transparency of water, and can also reduce photosynthesis in water bodies, even when present at very low concentrations (~10 ppm) 3,4 . In addition, some dyes are highly mutagenic and carcinogenic to living organisms, including humans 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Discharge of chemically stable and non-biodegradable toxic organic dyes into aquatic environments is a growing problem because of their highly toxic nature 1,2 . Organic dyes can affect the oxygen dissolution, sunlight penetration, and transparency of water, and can also reduce photosynthesis in water bodies, even when present at very low concentrations (~10 ppm) 3,4 . In addition, some dyes are highly mutagenic and carcinogenic to living organisms, including humans 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The narrow‐scan spectra for the modified membrane are displayed in Fig 3. It is observed that the C 1s spectrum of the unmodified membrane had only a single type of peak, CC/CH at 283.7 eV, whereas the core C 1s level spectrum of the modified membrane could be deconvoluted into three satellite peaks: 283.3 eV (CC), 284.5 eV (CC or CH) and 286.09 eV (CN or CCOH) 57,63,64 . Further, the N 1s spectrum can be resolved into three peaks related to different forms of nitrogen that are present in polyaniline.…”
Section: Resultsmentioning
confidence: 98%
“…Several methods were used to remove MV from water including photocatalytic reaction (31,32). Photocatalyst is a semiconductor substance that is activated when exposed with light irradiation, and it can participate in oxidation and reduction reactions (33)(34)(35). Recently, it has been reported that elemental ɑ-sulfur (S 8 ) can be used as photocatalyst for degradation of Rhodamin B (RhB) under visible light (36,37).…”
Section: Introductionmentioning
confidence: 99%